Methadone Maintenance Therapy after Aneurysmal Subarachnoid Hemorrhage: A Case Report - Smith, Austin; Cook, Aaron; Hatton, Kevin (McGill Journal of Medicine, 2023)
There is limited information on the effects of continued methadone maintenance therapy following aneurysmal subarachnoid hemorrhage (aSAH). However, with the increasing incidence of opioid use disorder (OUD) in the US, there is a need to define best practices for the management of pain and prevention of acute withdrawal syndrome in patients with pre-existing OUD who develop aSAH. In this case report, we describe the use of MMT in a patient with aSAH and discuss important considerations, including sedation or confusion that might mimic acute neurologic changes seen in cerebral vasospasm or delayed cerebral ischemia, cardiac complications related to QTc prolongation, and liver or kidney interactions associated with aSAH routine treatment. Our patient recovered from her aSAH without any adverse events and, with increased monitoring and collaborative team-based care, including input from those with expertise in OMD or aSAH, we believe MMT can be safely continued in most aSAH patients.